Digital Whoness : Identity, Privacy and Freedom in the Cyberworld. - Eldred, Michael (De Gruyter, 2013)
The first aim is to provide well-articulated concepts by thinking through elementary phenomena of today's world, focusing on privacy and the digital, to clarify who we are in the cyberworld - hence a phenomenology of digital whoness. The second aim is to engage critically, hermeneutically with older and current literature on privacy, including in today's emerging cyberworld. Phenomenological results include concepts of i) self-identity through interplay with the world, ii) personal privacy in contradistinction to the privacy of private property, iii) the cyberworld as an artificial, digital di.